2008
DOI: 10.1038/nature07178
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin and development of snake fangs

Abstract: Many advanced snakes use fangs-specialized teeth associated with a venom gland-to introduce venom into prey or attacker. Various front- and rear-fanged groups are recognized, according to whether their fangs are positioned anterior (for example cobras and vipers) or posterior (for example grass snakes) in the upper jaw. A fundamental controversy in snake evolution is whether or not front and rear fangs share the same evolutionary and developmental origin. Resolving this controversy could identify a major evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
136
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 20 publications
2
136
1
7
Order By: Relevance
“…However, our results also revealed that only two of the nine toxin families (crotamine and veficolin) contained a strongly supported monophyletic clade of snake toxins (Table 1), although the monophyly of snake toxins was also not rejected in the cystatin and hyaluronidase gene trees ( Table 2). As the single origin of venom in advanced snakes is strongly supported by multiple independent sources of evidence 2,4,5 , this suggests that the non-monophyly of their toxins may instead be due to multiple, independent recruitment events or as the result of reverse recruitment. Logically, those same phenomena, rather than multiple independent origins of venom, may also be responsible for the non-monophyly of Toxicoferan toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results also revealed that only two of the nine toxin families (crotamine and veficolin) contained a strongly supported monophyletic clade of snake toxins (Table 1), although the monophyly of snake toxins was also not rejected in the cystatin and hyaluronidase gene trees ( Table 2). As the single origin of venom in advanced snakes is strongly supported by multiple independent sources of evidence 2,4,5 , this suggests that the non-monophyly of their toxins may instead be due to multiple, independent recruitment events or as the result of reverse recruitment. Logically, those same phenomena, rather than multiple independent origins of venom, may also be responsible for the non-monophyly of Toxicoferan toxins.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the venom apparatus of squamates has been the subject of considerable recent research interest. The homology of the venom apparatus across the advanced snakes (Caenophidia) is robustly supported by anatomical evidence [1][2][3][4] , as well as comparative embryology and developmental genetics 5 . A recent addition to the body of evidence supporting the single early evolution of venom in snakes has been the use of protein amino acid or DNA gene sequences from toxins, and their homologues among non-venom body proteins 6,7 .…”
mentioning
confidence: 99%
“…These venoms, which consist of a complex mixture of toxic components, are usually delivered into their victims via bites or stings (2). The targeting of mammalian species by venomous animals has presumably introduced evolutionarily relevant selective pressures to either avoid or minimize the toxic effects of envenomation (3).…”
mentioning
confidence: 99%
“…Possuem um aparelho inoculador solenóglifo (as maxilas possuem apenas um par de dentes funcional agudo e oco) (MELGAREJO et al, 2003). Em associação ao aparato inoculador, estão presentes as glândulas de peçonha na região pós-orbital e, quando comprimidas por músculos acessórios, secretam seu conteúdo (JACKSON, 2007;FRY et al, 2008;VONK et al, 2008). A subfamília Crotalinae, incluída na família Viperidae, apresenta um par de fosseta loreal, um órgão que é termorreceptor e se encontra localizado entre a narina e o olho da serpente.…”
Section: Serpentes Do Brasilunclassified